MADS-Box Genes Are Key Components of Genetic Regulatory Networks Involved in Abiotic Stress and Plastic Developmental Responses in Plants - Castelán-Muñoz, Natalia; Herrera, Joel; Cajero-Sánchez, Wendy; Arrizubieta, Maite; Trejo, Carlos; García-Ponce, Berenice; Sánchez, María de la Paz; Álvarez-Buylla, Elena R.; Garay-Arroyo, Adriana (Frontiers in Plant Science, 2019)
Plants, as sessile organisms, adapt to different stressful conditions, such as drought, salinity, extreme temperatures, and nutrient deficiency, via plastic developmental and growth responses. Depending on the intensity and the developmental phase in which it is imposed, a stress condition may lead to a broad range of responses at the morphological, physiological, biochemical, and molecular levels. Transcription factors are key components of regulatory networks that integrate environmental cues and concert responses at the cellular level, including those that imply a stressful condition. Despite the fact that several studies have started to identify various members of the MADS-box gene family as important molecular components involved in different types of stress responses, we still lack an integrated view of their role in these processes. In this review, we analyze the function and regulation of MADS-box gene family members in response to drought, salt, cold, heat, and oxidative stress conditions in different developmental processes of several plants. In addition, we suggest that MADS-box genes are key components of gene regulatory networks involved in plant responses to stress and plant developmental plasticity in response to seasonal changes in environmental conditions.